Determinants of Hypertension Status among Patients with Type 2 Diabetes Mellitus at Menteng Primary Health Center, 2024–2025 - Haryoso, Ira Susanti; Radityadana, Yudha; Mufallahah, Muthik Hanim; Rahmartani, Lhuri Dwianti (Jurnal Epidemiologi Kesehatan Indonesia, 2026)
Hypertension is a common comorbidity in patients with type 2 diabetes mellitus (T2DM) and substantially increases the risk of both macrovascular and microvascular complications. Data on the determinants of hypertension status among T2DM patients in primary healthcare settings remain limited. This study aimed to analyze the determinants of hypertension status in T2DM patients at Puskesmas Menteng during 2024–2025. This was an analytic observational study employing a cross-sectional design. Study subjects comprised T2DM patients registered and undergoing examinations at Puskesmas Menteng over the 2024– 2025 period. Data were extracted from electronic medical records, included age, sex, occupation, socioeconomic status, blood pressure, hypertension status, diabetes duration, body mass index (BMI), kidney function (estimated glomerular filtration rate; eGFR), total cholesterol, low-density lipoprotein cholesterol, triglycerides, and urinary albumin. Hypertension status was classified as hypertensive or non-hypertensive. Multivariable logistic regression analysis was performed, and the results were reported as adjusted odds ratios (aORs) with 95% confidence intervals (CIs). A total of 462 patients with T2DM were analyzed, including 349 patients (75.5%) with hypertension and 113 patients without hypertension. In the multivariable analysis, obesity was significantly associated with increased odds of hypertension (aOR 2.36; 95% CI:1.17–4.78;p=0.017). Microalbuminuria (aOR 1.82;95%CI:1.11–3.00;p=0.019) and macroalbuminuria (aOR 3.47;95%CI:1.29–9.32;p=0.014) were also significantly associated with hypertension. HbA1c levels <7% were positively associated with hypertension status, whereas associations with eGFR categories should be interpreted with caution due to limited sample size and wide confidence intervals in advanced kidney function categories. These findings highlight the importance of weight control, monitoring kidney function monitoring, and early detection of albuminuria in preventing and controlling hypertension among patients with type 2 diabetes mellitus in primary healthcare settings.Keywords: Type 2 diabetes mellitus, Hypertension,  Glycemic Control, Hemoglobin  A1c, Primary Health Care